Cynicism in the Indian I.T. Organizations: An Exploration of the Employees` Perspectives - Dhar, Rajib Lochan (Qualitative Sociology Review, 2009)
Cynicism is described as a mind-set characterized by hopelessness, disappointment, and disillusionment, and is also associated with scorn, disgust, and suspicion. This strong negative attitude has infiltrated Indian I.T organizations, and is believed to be responsible for unfavorable organizational consequences, even though, hardly any studies have explored the causes and concerns of employee cynicism about their organizations in the Indian context. The present research centers around two qualitative case studies through in-depth interviews with seventy two participants undertaken in western India to investigate the causes and concerns of employee cynicism towards employer organization. Findings of the study indicate that workplace perceptions significantly influence organizational cynicism, which is largely influenced by poor leadership, organizational politics, decisive culture, accessibility of benefits and un-met expectations. As these findings have important organizational implications, I recommend for further studies on cynicism in the future.